2011
DOI: 10.1016/j.freeradbiomed.2010.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Substrate and inhibitor specificities differ between human cytosolic and mitochondrial thioredoxin reductases: Implications for development of specific inhibitors

Abstract: The cytosolic and mitochondrial thioredoxin reductases (TrxR1 and TrxR2) and thioredoxins (Trx1 and Trx2) are key components of the mammalian thioredoxin system, which is important for antioxidant defense and redox regulation of cell function. TrxR1 and TrxR2 are selenoproteins generally considered to have comparable properties, but to be functionally separated by their different compartments. To compare their properties we expressed recombinant human TrxR1 and TrxR2 and determined their substrate specificitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 54 publications
2
89
0
Order By: Relevance
“…The present data in the field indicates that the cytosolic TR is much more dependent on selenium for catalyzing the reduction of a diverse array of substrates (91). Furthermore, a recent study (65) showed that mitochondrial and cytosolic TRs present significantly different responses to metal compounds, for example, various gold(I) compounds were found to inhibit either one or the other (and not both) isozymes. The reason for this is still unclear: it may be that cytosolic and mitochondrial TRs have different local features (e.g., structure around their active sites, local flexibility, etc.)…”
Section: Hondal Et Almentioning
confidence: 63%
“…The present data in the field indicates that the cytosolic TR is much more dependent on selenium for catalyzing the reduction of a diverse array of substrates (91). Furthermore, a recent study (65) showed that mitochondrial and cytosolic TRs present significantly different responses to metal compounds, for example, various gold(I) compounds were found to inhibit either one or the other (and not both) isozymes. The reason for this is still unclear: it may be that cytosolic and mitochondrial TRs have different local features (e.g., structure around their active sites, local flexibility, etc.)…”
Section: Hondal Et Almentioning
confidence: 63%
“…(JUG), auranofin (AUR), myricetin (MYR), and curcumin (CUR) (Cai et al, 2012;Fang et al, 2005;Lu and Holmgren, 2012;Lu et al, 2006;Omata et al, 2006;Rackham et al, 2011). Figure 2B shows that the inhibition of the BoNT/A-mediated cleavage of SNAP25 by these inhibitors is dose dependent.…”
Section: Inhibitors Of Thioredoxin Reductase Prevent the Intoxicationmentioning
confidence: 95%
“…However, both the cytosolic and mitochondrial forms of TrxR possess a super active selenocysteine that is very sensitive to inactivation by electrophilic compounds (35,44). Upon extensive inactivation of TrxR, Trx will not be reduced effectively, and increased levels of oxidized Trx will result in cell death.…”
Section: Overexpression Of Grx2 In Hela Cells Provides Protection Agamentioning
confidence: 99%